Significant factors that enhanced local Small Medium Enterprises (SMEs) / Yusbi Helmi Mohd Yunus - Mohd Yunus, Yusbi Helmi (2010)
The main objective of this research project is to conduct an exploratory study on the relationship between factors that might influence SMEs to go internationally and internationalization itself. The paper will proceed as follows. First, some theories of internationalization, which are especially related to small firms, will be discussed. Then, we will identify factors that can be hypothesized to influence the international activities of small firms. Thereafter follows a method section in which the sample and variables of empirical study will be presented. Then the result of analysis will be discussed, and the paper will end with conclusions on future researches. At the end of chapter five, a some recommendations is proposed to encourage SMEs to go internationally. Based on this findings, all collected data will be analyze to get the significant factors that might enhanced or stimulate the participation of SMEs in international business.